2001
DOI: 10.1152/jappl.2001.91.6.2742
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone-induced relaxation of rat aorta is androgen structure specific and involves K+channel activation

Abstract: Recent studies have established that testosterone (Tes) produces acute (nongenomic) vasorelaxation. This study examined the structural specificity of Tes-induced vasorelaxation and the role of vascular smooth muscle (VSM) K+ channels in rat thoracic aorta. Aortic rings from male Sprague-Dawley rats with (Endo+) and without endothelium (Endo-) were prepared for isometric tension recording. In Endo- aortas precontracted with phenylephrine, 5-300 microM Tes produced dose-dependent relaxation from 10 microM (4 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
109
1
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(123 citation statements)
references
References 40 publications
10
109
1
1
Order By: Relevance
“…In contrast to studies on the SV, the experiments for hollow organs usually use a ring preparation, for example, studies investigating the effects of sildenafil on human penile blood vessels 12 and testosterone-induced vasodilatory effects of the rat aorta. 17 Similarly, In vitro bath studies could provide more accurate and physiologic results with the ring technique which preserves the natural tubular structure of the SV. In addition, the ring technique demands less manipulation and time to prepare the tissue specimen than the strips; therefore, the ring technique can minimize the hypoxic damage and destruction of the tissue integrity associated with the manipulation of these tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to studies on the SV, the experiments for hollow organs usually use a ring preparation, for example, studies investigating the effects of sildenafil on human penile blood vessels 12 and testosterone-induced vasodilatory effects of the rat aorta. 17 Similarly, In vitro bath studies could provide more accurate and physiologic results with the ring technique which preserves the natural tubular structure of the SV. In addition, the ring technique demands less manipulation and time to prepare the tissue specimen than the strips; therefore, the ring technique can minimize the hypoxic damage and destruction of the tissue integrity associated with the manipulation of these tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Further support for these observations came from recent studies on the relationship between testosterone supplementation and erectile dysfunction (ED). [16][17][18][19] Until the last decade such evidence was unclear; the role of androgen supplementation in sexual function was believed to be derived from its effect on sexual interest and libido. 16 Furthermore, experimental animal and human studies have demonstrated that androgens, primarily testosterone, play an important role in the vasculature of the corpus cavernosum of the penis.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies in the rat and rabbit have demonstrated a variety of biochemical changes in erectile function and structure that depend on adequate androgen levels. [17][18][19] In humans, the effects of testosterone supplementation have been studied in hypogonadal men with ED. 20 In 15 men with severe hypogonadism and a control group of 20 men with psychogenic ED, testosterone treatment for 6 months with a 5 mg/day patch normalized nocturnal penile tumescence parameters and improved penile vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Testosterone also has a permissive role in erectile function, which is not exclusively NO-dependent and induces acute (nongenomic) vasorelaxation via K þ channel activation of vascular smooth muscle cells. 5 Castration, besides leading to reduced NOS expression, also appeared to modify phosphodiesterase type-5 (PDE-5) gene expression in a rabbit model. 6,7 Recent evidence suggests that androgens may directly control the expression and activity of PDE-5 in the human corpus cavernosum.…”
Section: Introductionmentioning
confidence: 99%